2004
DOI: 10.1677/joe.0.1800167
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the effect of leptin on immune function in vivo using diet-induced obese mice

Abstract: Leptin can regulate several immune functions. However, the role of leptin on lymphocyte function has not been recognized in vivo. Accordingly, we have investigated the effect of leptin on starvation-induced immune dysfunction using diet-induced obese mice. To induce obesity, C57BL/6J mice were fed a high-fat diet for 14 weeks and control mice were fed a standard diet for the same period. The obese and control groups of mice were then starved for 48 h, and received intraperitoneal injections of recombinant lept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 29 publications
(33 reference statements)
1
20
0
5
Order By: Relevance
“…In vitro studies in diet-induced obese mice have shown that LPS stimulates proliferation of cultured splenocytes and that PHA stimulated production of certain cytokines (IFN-␥ and IL-10), but not all (IL-2) (80). In vivo studies in fasting diet-induced obese mice showed that leptin administration prevents pre-and poststarvation reduction in spleen weight compared with lean controls, but does not affect cytokine production (IL-2, IL-10, IFN-␥) in these mice, implying that the effect of leptin on immune cells in the obese state may be insignificant (81). Although our initial studies in humans (see above) are consistent with these findings in mice, it remains to be fully examined to which extent leptin influences the immune system and/or contributes to infections more frequently seen in patients with obesity.…”
Section: Future Directionsmentioning
confidence: 95%
“…In vitro studies in diet-induced obese mice have shown that LPS stimulates proliferation of cultured splenocytes and that PHA stimulated production of certain cytokines (IFN-␥ and IL-10), but not all (IL-2) (80). In vivo studies in fasting diet-induced obese mice showed that leptin administration prevents pre-and poststarvation reduction in spleen weight compared with lean controls, but does not affect cytokine production (IL-2, IL-10, IFN-␥) in these mice, implying that the effect of leptin on immune cells in the obese state may be insignificant (81). Although our initial studies in humans (see above) are consistent with these findings in mice, it remains to be fully examined to which extent leptin influences the immune system and/or contributes to infections more frequently seen in patients with obesity.…”
Section: Future Directionsmentioning
confidence: 95%
“…kines, which are bioactive molecules secreted from adipose tissue, are involved in energy metabolism, vascular homeostasis, and the immune response (1)(2)(3)(4)(5). Obesity results from excess accumulation of adipose tissue with hypertrophy and hyperplasia of adipocytes (5)(6)(7)(8)(9), which leads to abnormal secretion of adipocytokines (6,7) and triggers various diseases, including diabetes and cardiovascular diseases (2,6,7,10).…”
mentioning
confidence: 99%
“…Obesity results from excess accumulation of adipose tissue with hypertrophy and hyperplasia of adipocytes (5)(6)(7)(8)(9), which leads to abnormal secretion of adipocytokines (6,7) and triggers various diseases, including diabetes and cardiovascular diseases (2,6,7,10). Although these morphofunctional modifications of adipocyte are related to cell adhesion molecules, such as integrins (11,12), the precise molecular mechanisms behind the adipocyte growth (referred to as adipogenesis) in obesity are not fully understood.…”
mentioning
confidence: 99%
“…O envolvimento desse hormônio sobre o sistema imunológico também é alvo de pesquisa recente (HOWARD et al, 1999;SAVINO, 2002;MITO et al, 2004;SCHAIBLE e KAUFFMANN, 2007). A hipótese de que em estado de desnutrição há um desequilíbrio na produção de leptina.…”
Section: Desnutrição Exercício E Sistema Imunológicounclassified
“…Outros estudos voltaram a sua atenção para o envolvimento desse hormônio com a regulação do sistema imunológico (HOWARD et al, 1999;SAVINO, 2002;MITO et al, 2004;SCHAIBLE e KAUFMANN, 2007). Hipotetiza-se que em estado de desnutrição há um desequilíbrio na produção de leptina, que seria responsável de proteger os órgãos linfóides (HOWARD et al, 1999;FANTUZZI e FAGGIONE, 2000;SAVINO, 2000;BLÜHER e MANTAZOROS, 2004).…”
Section: Desnutriçãounclassified